Determination of the molecular mechanism(s) involved in the pro-apoptotic activity of momordica balsamina acetone extract in lung A549 cancer cells - Mudalahothe, Maedza (My University, 2019)
Plant-derived products have been used for years in the treatment of various ailments with low or no side effects. Thus, screening of medicinal plants for potential anticancer activity, in vitro, could help identify plant extracts or compounds that can be developed for use as anticancer agents with less or no side effects. The aim of this study was to investigate the probable anticancer effects and induced mechanism of action of Momordica balsamina crude leaf acetone extract in lung A549 cancer cells. The effect of the extract on cell viability, proliferation and cell division cycle were determined using Muse count & viability, Ki67 proliferation and cell cycle assay kits, respectively. The presence of biochemical and morphological features associated with apoptosis were analysed by Muse annexin-V & dead cell assay kit and Acridine orange/Ethidium bromide dual staining. The effect of the extract on the mRNA expression levels of cell cycle regulatory genes was determined using RT PCR. Proteome profiler antibody array was used to determine the effect of the extract on the protein expression levels of apoptosis regulatory genes. The findings revealed that the crude leaf acetone extract of M. balsamina decreased the percentage viability of lung A549 cells with less effect on the percentage viability of normal cells (KMST-6). Furthermore, a significant anti-proliferative effect in extract treated A549 cells was observed. Characteristic nuclear and morphological features of apoptosis such as chromatin and nuclear condensation, externalisation of phosphatidylserine and loss of cell membrane function were observed in A549 cells treated with the extract. Although there was no relative upregulation of Bax and Bad protein expression, a downregulation of the Bcl-xl and Bcl-2 protein expression was observed in extract-treated cells. This led to the release of Cytochrome c and HTRA2/Omi leading to pro-caspase-3 cleavage. Furthermore, presence of HTRA2/Omi in the cytosol inhibited the functions of IAPs such as XIAP and cIAP1/2. Phosphorylation of p53 at different serine residues led to upregulated protein expression levels of p27/Kip1 protein which resulted in the cell division cycle arrest at G0/G1-phase. Reverse transcriptase polymerase chain reaction results showed that the extract modulated mRNA expression levels of p53, p21, cyclin B and cdc2 genes. In summary, M. balsamina extract induced cell division cycle arrest and apoptosis in A549 cells through intrinsic apoptosis pathway via p53-mediated mechanism.
Thesis (M. Sc. (Biochemistry)) -- University of Limpopo, 2021
Keywords: Plant-derived products; Low side effects; Anticancer agents; Anticancer effects; Momordica balsamina; Antineoplastic agents; Antinoeplastic antibiotics; Medicinal plants; Mormodica